Isotriviality and étale cohomology of Laurent polynomial rings - Gille, Philippe (2008)
We provide a detailed study of torsors over Laurent polynomial rings under the action of an algebraic group. As applications we obtain variations of  Raghunathan´s result on torsors over affine space, isotriviality results for reductive group schemes and forms of algebras, and decomposition properties for Azumaya algebras.